Nondestructively decorating surface textured silicon with nanorod arrays for enhancing light harvesting (Phys. Status Solidi A 12∕2013). Issue 12 (December 2013) - Dong, Wenjing; Huang, Chanyan; Wei, Tiaoxing; Zhang, Yun; Zhang, Kenan; Sun, Yan; Chen, Xin; Dai, Ning
<x xml:space="preserve">Abstract</x> Minimizing surface reflection is among the key issues for enhancing light collection and therefore increasing the conversion efficiency of solar irradiance to electric energy for photovoltaic (PV) cells. In the study by Dong et al. (pp. 2542–2549), the surface of textured silicon solar cells is nondestructively decorated with ZnO nanorod arrays (ZNAs) in order to harvest more light. Without surface destruction during atomic layer deposition and hydrothermal processes, the ZNA layers are directly grown on the upper surface of commercial silicon cells with textured surface coated with SiNx layer. The scanning electron microscopy images of crystalline silicon (c‐Si) and multicrystalline silicon (mc‐Si) cells as well as those decorated with ZNAs show that their surfaces have different textured morphology, while the ZNA decorations are designed according to the varying textures of the c‐Si and mc‐Si cells. Accordingly, the surface reflections of both the decorated c‐Si and mc‐Si cells significantly reduce, which can be seen from the reflectance curves. Such antireflection decorations will open up more opportunities in feasible and compatible nonreflecting layers towards an optimal light harvesting for photoelectronic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>